A Multi-Robot Control Architecture for Fault-Tolerant Sensor-Based Coverage - Metin Ozkan; Gokhan Kirlik; Osman Parlaktuna; Alpaslan Yufka; Ahmet Yazici (International Journal of Advanced Robotic Systems, 2010)
Sensor-based coverage problems have many applications such as patrolling, search-rescue, and surveillance. Using multi-robot team increases efficiency by reducing completion time of a sensor-based coverage task. Robustness to robot failures is another advantage of using multiple robots for coverage. Although there are many works to increase the efficiency of coverage methods, there are few works related to robot failures in the literature. In this paper, fault-tolerant control architecture is proposed for sensor-based coverage. Robot failures are detected using the heartbeat strategy. To show the effectiveness of the proposed approach, experiments are conducted using P3-DX mobile robots both in laboratory and simulation environment.